Lonely mentality in Lv Bicheng’s ci poetry - Lai, Huey Yann (2016)
Lv Bicheng was a great woman among Chinese poetry and Women’ Society in the early 21st century. She was crowned as one of the modern female poets by Qian Chonglian. Originated from an aristocratic family, she was also a talented and intelligent person since young. She had made a name for herself. However, her life changed when her father passed on. With her strong character, she didn’t compromise to her life; she broke through the Feudalism thinking ‘It is a virtue for women without talent’. She left and begun a journey of her very own, setting foot to the stage of the world. In different stages of life of Lv Bicheng, she played different roles in the society and she took up different responsibilities both in society and in religion. Thus, she painted her own colourful legendary life. In her youth, Lv Bicheng filled with enthusiasm to defend women’s right as she was inspired by the modern women’s liberation thinking. She became an outstanding independent woman pioneer. In her late middle age, she went to the United States to study. After a few years, she put down everything, devoted herself to Buddhism. She advocated no killing and became an influential kulapati internationally. In Lv Bicheng’s life, she potrayed herself as a modern woman between the late Qing Dynasty and the Republic of China. Nevertheless, her identity did not change. She adhered in using classical Chinese to indite in her writings. She was referred as a classical literature rear-guard in the end of her life. This study will be looking at Lv Bicheng’s attitude in her solitary state, social circle and religion which happened in different times. It analyzes from the aspects of her solitary attitude to her poem and writings and how it changed from different era and religion where transformation had taken place that she became a modern woman with a high position and value.